Chela Reyes´ Acuatic Venus (ALPHA. Journal of Arts, Literature and Philosophy, 2020)
Chela Reyes (1904-1988) is a chilean writer born in Santiago, the same year as Pablo Neruda. She has a relevant poetic production, almost unknown, that can and should be considered as part of the tradition of the Chilean historical avant-garde. This work aims to show how, in Ola nocturna, her third book of poems published in 1945, the author uses characters and references from Greek mythology to shape her imaginary. Its figurative universe is constituted by powerful evocations of a maritime space in which Eros and Thanatos are confused. Characters such as Eolo, Hippocampus, Sirens, Neptune, Echo, Venus, are part of its mythological-poetic gallery. Through these figures the poet builds a surprising and fascinating world in which eroticism is both creation and destruction.
Keywords: Chela Reyes; Chilean Poetry; Women and Vanguard; Sea; Classical Mythology